Early-Age-Onset Colorectal Cancer in Canada: Evidence, Issues and Calls to Action - Mary A. De Vera; Sharlene Gill; Shady Ashamalla; Dan Schiller; Darren R. Brenner; Clarence Wong; Petra Wildgoose; Mary Jane Esplen; Christopher Lieu; Roslyn Fitzpatrick; Dylan E. O’Sullivan; Filomena Servidio-Italiano (Current Oncology, 2022)
The inaugural Early-Age-Onset Colorectal Cancer Symposium was convened in June 2021 to discuss the implications of rapidly rising rates of early-age-onset colorectal cancer (EAO-CRC) in Canadians under the age of 50 and the impactful outcomes associated with this disease. While the incidence of CRC is declining in people over the age of 50 in Canada and other developed countries worldwide, it is significantly rising in younger people. Canadians born after 1980 are 2 to 2.5 times more likely to be diagnosed with CRC before the age of 50 than previous generations at the same age. While the etiology of EAO-CRC is largely unknown, its characteristics differ in many key ways from CRC diagnosed in older people and warrant a specific approach to risk factor identification, early detection and treatment. Participants of the symposium offered directions for research and clinical practice, and developed actionable recommendations to address the unique needs of these individuals diagnosed with EAO-CRC. Calls for action emerging from the symposium included: increased awareness of EAO-CRC among public and primary care practitioners; promotion of early detection programs in younger populations; and the continuation of research to identify unique risk factor profiles, tumour characteristics and treatment models that can inform tailored approaches to the management of EAO-CRC.